The Mobility Revolution in the Automotive Industry : How not to miss the digital turnpike - Wedeniwski, Dr. Sebastian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
The Internet of Things, cloud computing, connected vehicles, Big Data, analytics what does this have to do with the automotive industry? This book provides information about the future of mobility trends resulting from digitisation, connectedness, personalisation and data insights. The automotive industry is on the verge of undergoing a fundamental transformation. Large, traditional companies in particular will have to adapt, develop new business models and implement flexibility with the aid of appropriate enterprise architectures. Transforming critical business competencies is the key concept. The vehicle of the digital future is already here who will shape it?
Introduction -- Enterprise architectures: surrounded by historical structures -- Digitalisation of the industry from the AUTOmobile to the autoMOBILE -- Index.
Keywords: Computer science; Computer Science; Information Systems Applications (incl. Internet).